PENGARUH MODEL PEMBELAJARAN VALUE CLARIFICATION TECHNIQUE (VCT) TERHADAP SIKAP SEMANGAT KEBANGSAAN DAN SIKAP TOLERANSI PADA MATA PELAJARAN IPS KELAS V SD AISYIYAH KOTA SUKABUMI - Nurrohmatul Amaliyah; Dede Risma Ginanjar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the effect of the Value Clarification Technique (VCT) learning model on students’ nationalism spirit and tolerance attitude in social studies subjects at SD Aisyiyah Sukabumi City. The research employed a quantitative approach with a quasi-experimental method. The data source consisted of fifth-grade students divided into experimental and control groups. Data were collected through observation and attitude questionnaires on nationalism and tolerance. The findings showed that the VCT model had a significant effect on both variables, indicated by the t-test results of t = 3.512; Sig. = 0.001 < 0.05 for nationalism and t = 3.071; Sig. = 0.004 < 0.05 for tolerance. These results prove that the VCT model effectively fosters students’ national spirit and tolerance values. In conclusion, the VCT model can be an alternative strategy in social studies learning to strengthen students’ character education.